FBG-instrumented FDM support structure design guidelines and execution for torque and angular speed measurements in aerospace applications - Saturno, Gustavo; Cunha, João; Biazi-Neto, Vitorino; Moreira, Rui A.S.; Nedoma, Jan; Ioannou, Andreas; Kalli, Kyriacos; Martinek, Radek; Marques, Carlos (My University, 2025)
This paper introduces a novel approach to torque and angular speed measurement in aerospace systems by embedding Fiber Bragg Gratings (FBGs) directly into an additively manufactured polyethylene terephthalate glycol (PETG) motor support structure. Traditional electronic sensors, while effective, are prone to electromagnetic interference and mechanical complexity, critical challenges in aerospace environments. To address this, the proposed method leverages the support structure itself as the sensing mechanism, drastically simplifying integration. The structural integrity and strain performance were validated through Finite Element Method (FEM) simulations and experimental tests. A one-dimensional Kalman filter was implemented to address PETG's viscoelastic behavior, reducing torque estimation error from ±0.00284Nm to ±0.00093Nm. Angular speed measurements achieved a correlation of R2=0.9999 when compared to a reference tachometer. This work demonstrates that high-accuracy, compact, and robust FBG-based sensor systems can serve as scalable, lightweight alternatives for aerospace torque and RPM monitoring in the context of digitalization and predictive maintenance.
Keywords: Additive manufacturing; Aerospace sensors; Angular speed sensing; Fiber Bragg Gratings (FBG); Kalman filter; PETG support structure; Structural health monitoring; Torque measurement